Development of a Mikrotik API-Based Leaderboard System for Monitoring ISP User Activity - Yutanto, Hariadi; Effendi, Yusuf; Supriyanto, Gaguk (Diponegoro University, 2025)
The digital transformation has significantly increased the demand for fast, stable, and transparent internet access. The surge in internet users, particularly in the post-COVID-19 era, has made internet services a primary necessity. PT Olean Telematika as an Internet Service Provider (ISP) utilizing Fiber To The Home (FTTH) technology, needs to implement a monitoring system capable of displaying customer activity in real time as a form of service transparency. This study aims to develop and evaluate a leaderboard system based on Mikrotik API that presents bandwidth usage rankings of ISP customers. The system was developed using the Waterfall model and integrated with PHP and MySQL to manage customer upload and download activity dat. Rankings are visually displayed through a web-based interface. This paper evaluated the system using the System Usability Scale (SUS) instrument with 30 active users, resulting in an average score of 75.63, which falls into the “good” category. These results indicate that the system is not only functional but also positively received by users. The leaderboard system is effective in enhancing service transparency and supporting data-driven decision-making by ISPs to improve customer satisfaction.